The Inverse Bin-Packing Problem Subject to Qualitative Criteria - Furems, E. M. (Scientific and technical information processing, 2017)
A new formulation of the reverse bin-packing problem is suggested. One distinct feature of the new formulation is that it takes into account of a decision-maker’s preferences for a set of objects that are evaluated by multiple quality criteria. The aspects of this problem are discussed that relate to the theory of multiple criteria decision making. The known methods for solving the classic and the reverse bin-packing problems (the multiple knapsack problem) are reviewed.